Combined lubricant–surface system perspective: Multi-scale numerical–experimental investigation. (July 2017) - Leighton, M; Nicholls, T; De la Cruz, M; Rahmani, R; Rahnejat, H
Frictional losses are one of the main causes of reduced energy efficiency in all machines and mechanisms. In particular, there is mounting pressure upon manufacturers of all forms of vehicle to comply with increasingly stringent legislation and directives with regard to harmful emissions. Therefore, reduction of friction has become an imperative issue. The traditional approach of dealing with surface material and lubricant formulation in isolation has been replaced by a lubricant–surface system approach. This paper presents multi-scale experimentation from nano/meso-scale lateral force microscopy of ultra-thin surface adsorbed films through to micro-scale precision sliding tribometry to investigate lubricant–surface friction optimisation within the mixed regime of lubrication, using lubricants with different organic and inorganic friction modifying species. These affect the parameters of the system, commonly used as input to models for mixed and boundary regimes of lubrication. Therefore, the precise measurement of these parameters at different physical scales is important. The study also makes use of detailed numerical predictions at micro-scale through combined solution of the average Reynolds equation as well as interaction of wetted asperities in mixed and boundary regimes of lubrication. Good agreement is found between the predictions and measurements at micro-scale tribometric interactions. Furthermore, the same trends are observed in testing across the physical scales.